Protein restriction cycles reduce IGF‐1 and phosphorylated Tau, and improve behavioral performance in an Alzheimer's disease mouse model. Issue 2 (11th March 2013) - Parrella, Edoardo; Maxim, Tom; Maialetti, Francesca; Zhang, Lu; Wan, Junxiang; Wei, Min; Cohen, Pinchas; Fontana, Luigi; Longo, Valter D.
Summary In laboratory animals, calorie restriction (CR) protects against aging, oxidative stress, and neurodegenerative pathologies. Reduced levels of growth hormone and IGF‐1, which mediate some of the protective effects of CR, can also extend longevity and/or protect against age‐related diseases in rodents and humans. However, severely restricted diets are difficult to maintain and are associated with chronically low weight and other major side effects. Here we show that 4 months of periodic protein restriction cycles (PRCs) with supplementation of nonessential amino acids in mice already displaying significant cognitive impairment and Alzheimer's disease (AD)‐like pathology reduced circulating IGF‐1 levels by 30–70% and caused an 8‐fold increase in IGFBP‐1. Whereas PRCs did not affect the levels of β amyloid (Aβ), they decreased tau phosphorylation in the hippocampus and alleviated the age‐dependent impairment in cognitive performance. These results indicate that periodic protein restriction cycles without CR can promote changes in circulating growth factors and tau phosphorylation associated with protection against age‐related neuropathologies.